(untitled) (Research, Society and Development, 2022)
Acute myocardial infarction is among the leading causes of morbidity and mortality worldwide. Based on this, strategic actions aimed at controlling risk factors are essential to reduce the incidence, sequelae and mortality from the disease. Furthermore, understanding the profile of affected individuals and the local specificities linked to the occurrence is essential for health planning. Thus, the objective was to analyze the characteristics and distribution of deaths from acute myocardial infarction in the state of Paraná, between 2019 and 2020. This is a descriptive study, in which death notifications were analyzed, based on the System of Mortality information. Data were presented with absolute and relative frequency, as well as mortality rates and percentage change. Between 2019 and 2020, 9,133 deaths were recorded. A predominance of deaths was identified among male individuals, married marital status, aged 60 years or older, of white race/color and with 1 to 7 years of schooling. The most frequent place of occurrence was the hospital environment, followed by the home environment. Regarding distribution, mortality rates were higher in the Northwest Macroregion. In the variation between years, there was a greater increase in the West macro-region and a decrease in the East. Furthermore, there was a significant increase in the 7th and 5th Regionals, and a reduction in the 16th and 4th Regionals. In this sense, it is necessary to highlight the singularities that exist in the state, in order to understand the dynamics of the disease at the local level and, consequently, direct strategies for the control and management of cases.